Dental, Dental Hygiene, and Advanced Dental Students' Use, Knowledge, and Beliefs Regarding Tobacco Products. Issue 11 (1st November 2017) - Shearston, Jenni A.; Shah, Krina; Cheng, Eric; Moosvi, Rizvan; Park, Su Hyun; Patel, Naiya; Spielman, Andrew I.; Weitzman, Michael L.
Abstract : Using cigarettes and alternative tobacco products (ATPs) is associated with negative oral health outcomes, and dental health professionals are poised to help patients quit. The aim of this study was to determine dental, dental hygiene, and advanced dental students' use, knowledge, and beliefs about cigarettes and ATPs, including perceptions about their education in tobacco dependence treatment and counseling experience. All 1, 783 students enrolled in the dental, dental hygiene, and postdoctoral dental programs at the New York University College of Dentistry were invited to participate in the survey in 2016. A total of 708 students at least partially completed the survey, for a response rate of 39.7%. In the results, 146 of the students (20.1%) reported ever using cigarettes, while 253 (35.7%) reported ever using any ATP. Regarding tobacco use intervention, the students reported they had not received enough training on ATPs, were neutral about cigarettes, and were somewhat confident and not so confident counseling a cigarette smoker or ATP user, respectively. By their fourth year, 77.8% of the dental students reported they had counseled someone to stop smoking cigarettes, but only 40.7% had counseled someone to stop using ATPs. Overall, all groups of students reported feeling more confident and had received more education on interventions for cigarettes than for ATPs (p<0.001). These students reported low confidence in helping people quit tobacco and did not perceive they had received enough training on intervening with patients on use of cigarettes and ATPs. These findings call for a revised tobacco education curriculum for dental, dental hygiene, and advanced dental students, focused on building knowledge and confidence for promoting tobacco dependence treatment.